THE IMPACT OF ARTIFICIAL INTELLIGENCE (AI) ON SUPPLY CHAIN DECISION-MAKING: A COMPREHENSIVE ANALYSIS - ANANTHARAMAN PRAKASH, Prof. Dr. C.B. SENTHIL KUMAR, Dr. D.K. JAYAKANTH (South Eastern European Journal of Public Health, 2025)
This research focuses on exploring the potential of artificial intelligence (AI) for revolutionizing the supply chain decision making environment in various industries. The study analyzes how AI technologies are revolutionizing traditional supply chain management approaches through enhanced predictive capabilities, automated decision support systems, and real-time optimization. A survey of 150 supply chain professionals across various industries was conducted to understand the adoption patterns, challenges, and benefits of AI implementation in supply chain operations. The findings reveal that organizations implementing AI-driven decision-making systems reported a 35% improvement in forecast accuracy, 28% reduction in inventory costs, and 42% enhancement in supplier relationship management. However, challenges related to data quality, integration complexity, and workforce adaptation remain significant barriers to widespread adoption. This research provides valuable insights for supply chain practitioners and researchers on effectively leveraging AI for strategic decision-making while addressing implementation challenges.